2015
DOI: 10.1007/s12529-015-9518-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Risk Factors for Unintentional Drowning Among Rural Chinese Children

Abstract: High exposure to water sources and non-fatal drowning experiences were found among school-aged children in rural China. Drowning risk factors included demographic, cognitive, and behavioral characteristics of children. Results offer evidence for developing interventions in both Zhejiang Province and other regions with similar geographic and population characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Child sex was not a confounding variable in this study, which contradicts previous findings that boys report increased swimming ability and reduced levels of perceived vulnerability. 24 These findings do, however, align with evidence that supports child sex has no influence on children's perceived locomotor competence (considering swimming is a type of locomotor skill). 17 Since this sample was all in lessons (currently or in the past), it is likely that they have better awareness of their competence than children who have never participated in lessons, and that this awareness was similar for both boys and girls.…”
Section: Discussionmentioning
confidence: 54%
“…Child sex was not a confounding variable in this study, which contradicts previous findings that boys report increased swimming ability and reduced levels of perceived vulnerability. 24 These findings do, however, align with evidence that supports child sex has no influence on children's perceived locomotor competence (considering swimming is a type of locomotor skill). 17 Since this sample was all in lessons (currently or in the past), it is likely that they have better awareness of their competence than children who have never participated in lessons, and that this awareness was similar for both boys and girls.…”
Section: Discussionmentioning
confidence: 54%
“…Risk factors for childhood drowning in LMICs include, but are not limited to, inadequate supervision, male sex, lack of physical barriers between people and water bodies, and lack of swimming ability [8,16,17,18]. Lack of water safety awareness, risky behavior around water, and perceived risk are also considered important risk factors [19,20,21]. Travelling on overcrowded or poorly maintained vessels and water related disasters (e.g., flood, extreme rainfall, storm surges, and tsunamis or cyclones) are also common risk factors in all age groups globally [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done in Bangladesh revealed that monsoon rainfalls can lead to floods with increased level of in rivers, canals, ponds, and ditches leading to higher risk of drowning among children and adults. 14 It was seen that majority of the cases took place during daylight hours. This pattern of season and time of drowning are also seen in this study.…”
Section: Discussionmentioning
confidence: 98%